Studi Kasus Penggunaan Gadget terhadap Perkembangan Bahasa Anak Usia 2-3 Tahun - Hidayat, Syifa Rahma (Bandung Conference Series: Early Childhood Teacher Education, 2025)
The high involvement of early childhoods in the use of gadgets, especially in children aged 2 to 3 years, is feared to have a negative impact on their language development. Many children are more accustomed to using gadgets than to communicating with their surroundings, which raises concern about speech delayed, insufficient vocabulary, and poor communication skills. This research is intended to gain an understanding of how patterns of use of gadgets by children and how these gadgets affest children’s language development at aged 2 to 3 years. This study utilizes qualitative methods trough a case study framework, Data were collected through in-depth interviews with parents, observations, and documentation. The study involved three children aged 2 to 3 years, each with different patterns of gadget use. These different patterns resulted in varied insights regarding the impact of gadget use on children's language development. The result of this study show that children who have used gadgets with high duration and frequency without parental assistance tend to experience problems in language development, such as speech delay, limited vocabulary, and language development. The pronunciation of sentences that are unclear and less responsive in communication. But, children who use gadgets with clear boundaries and parental guidance show more optimal language development. Gadget use affects the language development of children aged 2 to 3 years depending on the duration of use, type of content accessed, and the involvement of parents during gadget use.